Influence of pop-up media towards increasing the knowledge of dental and oral health of Students at SDN No.19 Limboro Majene - jdmfs jdmfs; Akbar; Nurul Hasrul; Alya KI. Day; Viky IM. Baharuddin; Wulan F. Lenggany; Asmawati (Journal of Dentomaxillofacial Science, 2021)
Objective: Dental caries is a disease caused by many factors. Low awareness for dental and oral health of the community in Limboro village is influenced by several factors which are difficulty of access to the village of Limboro, lack of access to dental and oral health information, and language barriers. By looking to this problems, Student Creativity Program students was giving health information in the form of pop-up book which contain educational stories about dental and oral health with attractive visualization. Material and Methods: The study was conducted with descriptive observational study by cross-sectional approach. 10 students from class 1,2,3 SDN No. 19 Limboro were taken as respondents. Students were given information and knowledge by using dental and oral education posters, and were involved in games and drama related to stories in pop-up books and joint toothbrush training and toothbrush exercises. By the end, pre-tests and post-tests using questionnaires were conducted. Result: The statistical analysis result shows the significant value is 0.089 <0.05, means there is a relationship between the variable pre-test and post-test. By using Paired-T-Test, there is a difference in the average pre-test and post-test results of respondent at SDN No. 19 Limboro. Conclusion: Study showed knowledge of students of SDN No. 19 Limboro was increased after the influence of pop-up media on improving dental and oral health.